The traveller as a concept’s translator: study of the hispanic and indigineous words in Der Wochenmarkt in Cartago (1853) (ALPHA. Journal of Arts, Literature and Philosophy, 2021)
The aim of this piece of work is to analyse the Hispanic and Indigenous words that are to be found in a German description of a market in Cartago written by Karl Ritter von Scherzer (1821-1903). In order to do that an ad hoc gradient (as a result of a compilation of philological, translation and cultural methodologies) will be applied. This analysis will show that there are some words that are either domesticated (a dynamic equivalence will be used) or foreignized (the terms will not be translated), so as the traveller-scientist is more than an intercultural intermediary: he is a translator of traditions and concepts.
Keywords: Travel literature; Costa Rica; 19th Century; Karl Ritter von Scherzer; Hispanic words; Indigenous words; Historical translation